The case of infectious diseases: severe systemic mycoses and their treatment with imidazole derivatives. Presentation of three cases - González, Aurelio; Naranjo V., María Soledad (Medicina UPB, 1987)
Three young patients (ages 7 21 years) with severe histoplasmosis or paracoccidioidomicosis were treated with imidazole compounds [ketoconazole 200 mg/day, itraconazole 100 mg/day) orally, for periods of 14 to 24 months. The patients began to improve after 2 months of therapy and achieved control of their infection with prolonged therapy, There were no alterations in the hematologic or hepatic function tests, nor were there side-effects_ These patients have been followed post therapy for over two years, with no signs of relapse. Clinical and laboratory tests indicate that the imidazole compounds used for the treatment of these patients constitute a valuable- alternative to amphotericin B for the therapy of severe mycoses.
Keywords: Deep Mycoses; Hitoplasmosis; Paracoccidioidomycosis; Itraconazole; Ketoconazole